Monsoon control on channel avulsions in the Late Quaternary Congo Fan. (15th January 2019) - Picot, M.; Marsset, T.; Droz, L.; Dennielou, B.; Baudin, F.; Hermoso, M.; de Rafelis, M.; Sionneau, T.; Cremer, M.; Laurent, D.; Bez, M.
Abstract: The mechanisms governing the development of deep-sea fans is a matter of debate and their understanding at Milankovitch and millenial time-scales is challenged by complex architectures and the lack of material suitable for establishing reliable chronostratigraphies. Based on a detailed investigation of the emplacement of channel-levee-lobe systems and their successive bifurcations and seaward-landward migrations (Picot et al., 2016), we present for the last 210 ka a detailed chronostratigraphic framework of the migration pattern based mainly on radiocarcarbon dating of channels and lobes abandonment or initiation. The comparison of architectural cycles to proxies of external factors (sea-level and climate) suggest that sea-level changes have minor impacts on the architectural evolution of the Congo Fan. In contrast, comparison with climate and environmental proxies (West African monsoon, pollen grain assemblages, Kaolinite/Smectite) evidences a major impact on the timing of the development of the architectural pattern, at least for the last 38 kyr. A general scheme of the growth pattern of the Congo Fan in link with climate evolution is proposed: the stacking pattern of the Congo Fan responds to humidity/aridity cycles that generate successive progradation and retrogradation of avulsion points. These climate changes are under the control of the West African monsoon which, by controlling the rainfall and vegetation on the watershed, ultimately impacts the composition and volume of the sediment source and the transport capacity of gravity flow generated in the canyon and flowing in the turbiditic channels.